Edible forests: building resilient communities through perennial fruit and nut production - Naim Edwards (Urban Food Systems Symposium, 2022)
Edible forests are landscapes made up of woody edible plants, and they have been growing in popularity across the U.S. Also known as food forests, these spaces integrate fruit and nut trees into streetscapes, parks, residential yards, private lands, etc. In addition to food production, edible forests address a variety of challenges communities face. These include economic, ecological, and social issues such as poverty, climate change, flooding, greenspace, and revenue streams. Understanding how to plan, implement, and manage edible forests is critical to their viability and longevity. Michigan State University Extension has established an edible forest in Detroit to study best management practices for sustaining these landscapes.
Keywords: urban agriculture; food; landscaping; trees